The Association between Central Adiposity and Autonomic Dysfunction in Obesity - Fidan-Yaylali, Güzin (Med Princ Pract, 2016)
OBJECTIVE: To determine the relationship between central adiposity parameters and autonomic nervous system (ANS) dysfunction. SUBJECTS AND METHODS: The study included 114 obese individuals without any cardiovascular risk factors. Weight (in kg), height (in m), and waist circumference (WC; in cm) were measured and body mass index was calculated. Echocardiographic examination was performed to measure left ventricular mass and epicardial fat thickness (EFT). All the participants underwent an exercise test and electrophysiological evaluation using electromyography. Heart rate recovery (HRR) at 1-5 min, R-R interval variation at rest and during hyperventilation, and sympathetic skin response were measured. Pearson's correlation analysis was used. Multiple linear regression analysis was used to identify the factors associated with autonomic dysfunction. RESULTS: The HRR at 1-5 min was negatively correlated with WC and age (WC-HRR1: r = −0.32; WC-HRR2: r = −0.31; WC-HRR3: r = −0.26; WC-HRR4: r = −0.23; WC-HRR5: r = −0.21; age-HRR2: r = −0.32; age-HRR3: r = −0.28; age-HRR4: r = −0.41; age-HRR5: r = −0.42). Age was the only independent predictor of reduced HRR at 1-5 min. In addition, WC predicted a reduced HRR at 3 min. There were no significant associations between central obesity and electrophysiological parameters. EFT was not associated with ANS dysfunction. CONCLUSION: In this study, central adiposity and aging were associated with ANS dysfunction in obese individuals. The WC could be a marker of ANS dysfunction in obese individuals without any cardiovascular risk factors. The HRR assessment at a later decay phase could be more valuable for evaluating ANS function than during early recovery.